A Permanent Multilevel Monitoring and Sampling System in the Coastal Groundwater Mixing Zones. Issue 4 (15th March 2017) - Luo, Xin; Kwok, King Lun; Liu, Yi; Jiao, Jimmy
Abstract: To study the spatial and temporal variability of water dynamics and chemical reactions within the coastal groundwater mixing zones (CGMZs), high‐resolution periodical and spatial groundwater sampling within CGMZs is needed. However, current samplers and sampling systems may require heavy driving machines to install. There is also possible contamination from the metal materials for current samplers and sampling systems. Here, a permanent multilevel sampling system is designed to sample coastal groundwater within CGMZs. This cost‐effective system consists of metal‐free materials and can be installed easily. The system is tested in Po Sam Pai and Tingkok, Tolo Harbor and Hong Kong. Major ions, nutrients, stable isotopes and radium and radon isotopes were analyzed and the data provided scientific information to study the fresh‐saltwater interface fluctuations, and temporal variations and spatial heterogeneity of geochemical processes occurred within CGMZs. The reliable spatial and temporal data from the sampling system demonstrate that the system functions well and can provide scientific data for coastal aquifer studies.